ANALISIS SEMIOTIKA PERSONAL BRANDING POLITISI PEREMPUAN DI MEDIA MAINSTREAM DAN MEDIA SOSIAL - Rido Latuheru; Ika Fransisca (Fakultas Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes the personal branding strategies of female politicians in mainstream media and social media using a semiotic analysis approach. The research aims to identify and analyze patterns, strategies, and effectiveness of female politicians' personal branding across various media platforms. Using qualitative methodology and Roland Barthes' semiotic analysis model, thisstudy examines mainstream media and social media content during the period of January- December 2023. The results show significant differences in personal branding strategies between mainstream media and social media, with social media providing greater narrative control but demanding higher authenticity. Research findings reveal the persistence of gender bias in mainstream media while demonstrating how female politicians utilize social media to counter these narratives. This research provides theoretical contributions in developing digital semiotic analysis models and understanding intersectionality in political communication, as well as practical contributions in the form of strategic guidelines for female politicians in building effective personal brands in the digital era.